Exploring hematological diversity, a comprehensive study of CBC variations among the population of Tehsil Kot-Momin Sargodha - Kamran Arzoo; Muhammad Aslam Shaikh; ZafarLatif Awan; Mudaser Hussain Abbasi; Awais Anwar; Amna Akram (Journal of University Medical & Dental College)
Objectives: To ascertain the diversity and patterns observed in the complete blood count within the population of Tehsil Kot-Momin , Sargodha.